Edukasi dan Konseling Kesehatan Mental di Kalangan Mahasiswa - Ilzana, Teuku Muhammad; Adelaidey, Asyrafun Nisa; Rambe, Irpan Efendi; Rifhan, Zanurul; Jayalie , Vito Filbert; Sulviani, Nurul (CV. Devi Tara Innovations, 2024)
This community service aims to increase students' awareness, understanding, and skills in maintaining mental health through education and counseling programs. Student life is often filled with academic, social, and adaptable pressures to a new environment that can trigger mental health problems such as stress, anxiety, and depression. The program includes seminars, workshops, and counseling sessions held at several colleges with a focus on introducing the importance of mental health, coping techniques, and appropriate psychological support. This activity involves students' active participation in discussions, role-plays, and simulations, which helps them better understand how to manage emotions and seek help when facing problems. The evaluation of the program showed an increase in students' knowledge and skills in dealing with mental health problems, as well as an increase in the number of students willing to access counseling services. Through this activity, it is hoped that a campus environment that is more supportive of mental health and reduces the stigma of seeking professional help.